2008
DOI: 10.1063/1.3002424
|View full text |Cite
|
Sign up to set email alerts
|

Probing thermal waves on the free surface of various media: Surface fluctuation specular reflection spectroscopy

Abstract: Thermal motion gives rise to fluctuations in free surfaces; measurement of the thermally excited waves on such surfaces provides information on the mechanical properties of the medium. We have developed an optical tool to probe the thermally excited waves on free surfaces: surface fluctuation specular reflection (SFSR) spectroscopy. It consists in measuring the fluctuations in the position of a laser beam that is specularly reflected onto the free surface of a medium. The position of the reflected beam is sens… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 17 publications
1
28
0
Order By: Relevance
“…Surface fluctuations, and its fluctuating position can be related to the fluctuating local slope of the liquid surface [16]. Such a measurement mixes the contributions from several surface modes, unlike a light scattering experiment in which a single spatial mode is selected.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Surface fluctuations, and its fluctuating position can be related to the fluctuating local slope of the liquid surface [16]. Such a measurement mixes the contributions from several surface modes, unlike a light scattering experiment in which a single spatial mode is selected.…”
Section: Methodsmentioning
confidence: 99%
“…Since, in each direction, we deal with signals that are normalized by the total intensity of the considered two quadrants, those signals can be compared even though the total intensity may slightly differ. We have shown that, taking into account the contributions from all the spatial modes of the surface, the PSD S(ω) can be approximated by [16] …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this work, we detect reflected light from surfaces to measure their inclinations [5][6][7] and apply this to thermal surface fluctuations of simple liquids. The measurements are somewhat complementary to the spectral measurements performed at specific wavelengths.…”
Section: Introductionmentioning
confidence: 99%